Analyses of seizure responses supportive of a novel trial design to assess efficacy of antiepileptic drugs in infants and young children with epilepsy: Post hoc analyses of pediatric levetiracetam and lacosamide trials. Issue 2 (3rd May 2021) - Johnson, Martin E.; McClung, Carrie; Bozorg, Ali M.
Abstract: Objective: Recently, a novel trial design has been proposed to overcome challenges with traditional placebo‐controlled trials of antiepileptic drugs in infants and young children (≥1 month of age) (Auvin S, et al. Epilepsia Open 2019;4:537‐43). The proposed time‐to‐event trial design involves seizure counting by caregivers and allows adjustment of the duration of the baseline period and duration of exposure to placebo or potentially ineffective treatment based on the patient's seizure burden and response. We performed post hoc analyses to mimic this trial design and evaluate its viability. As these analyses required trials with prolonged baseline and treatment periods and diary data, which is not a typical design of trials in infants and young children (1 month to <4 years of age), data from two trials in pediatric patients (4‐16 years of age) were used. Methods: We performed post hoc analyses of two randomized, double‐blind, placebo‐controlled trials of adjunctive levetiracetam (N159; NCT00615615) and lacosamide (SP0969; NCT01921205) in children and adolescents (4‐16 years of age) with focal‐onset seizures. In these analyses, patients were followed until they completed the 10‐week maintenance period, discontinued during the maintenance period, or reached their "nth" seizure (n = number of seizures patient had during baseline). Efficacy was assessed by determining time to nth seizure. Results: In the analyses of both trials, patients on levetiracetam or lacosamide had a 34% lower risk of reaching their baseline seizure count during their 10‐week maintenance period than patients on placebo. The previously published primary results of these trials also demonstrated efficacy of adjunctive levetiracetam and lacosamide. Significance: Although these were post hoc analyses of trials in older children (4‐16 years of age), our results provide supportive evidence for the utility of the novel time‐to‐event trial design for future trials in infants and young children (1 month to <4 years of age).